2011
DOI: 10.1002/app.34816
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polydimethylsiloxane (PDMS)/polytetramethyleneadipate glycol (PTAd)‐based waterborne polyurethane adhesives: Effect of PDMS molecular weight and content

Abstract: Waterborne polyurethane (WBPU) dispersions were prepared by pre‐polymer process using siloxane polyol, namely polydimethylsiloxane (PDMS), and polyester polyol, namely poly(tetramethyleneadipate glycol) (PTAd), as a soft segment. Three different molecular weights (Mn = 550, 6000, 110,000) of PDMS and one fixed molecular weight of PTAd (Mn = 2000) was used during preparation of WBPU dispersions. This research aims to explore the potential use of PDMS in complementing WBPU by boosting flexibility, water resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…This might be due to the lower adhesive strength when using higher PDMS content. 42 The coating using WBPU was covered with various marine foulers including juvenile barnacles, oysters, polycheates, and a thin slime of an algal mat.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the lower adhesive strength when using higher PDMS content. 42 The coating using WBPU was covered with various marine foulers including juvenile barnacles, oysters, polycheates, and a thin slime of an algal mat.…”
Section: Resultsmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) has unique properties such as low surface energy, hydrophobicity, high flexibility, transparency and excellent thermal, oxidative and UV stability. It has been shown that the adequate inclusion of PDMS prepolymers, such as hydroxyl-hexyl, aminopropyl, methyl aminopropyl PDMS into a WPU matrix can improve the water resistance and hydrophobic surface properties of WPU films [7][8][9][10][11]. However, their mechanical properties are not improved much and even decreased with high PDMS content due to the extremely high incompatibility between the urethane (or urea) and the PDMS segments.…”
Section: Introductionmentioning
confidence: 99%
“…1−5 Because of their interesting properties, polyurethanes are widely used as protecting coatings, 6 elastomers, 7 adhesives, 8 foams, 9 membranes, 10 medical implants, 11 biomaterials, 12−14 etc. Segmented polyurethanes (PURs) are copolymers usually composed of alternating soft (SS) and hard (HS) segments.…”
Section: Introductionmentioning
confidence: 99%